Pacing strategies in elite individual medley swimmers: A decision tree approach - CHANG, C. K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: This study aims to investigate the pacing strategy and the importance of the four different stroke in men`s and women`s 200- and 400-m individual medley competitions in Olympic Games and World Swimming Championships between 2000 and 2021, excluding 2008 to 2010. METHODS: The time in each lap and overall race were retrieved from the World Aquatics website. The final data comprised a total of 1937 data points (1052 for men, 885 for women) for the 200-m event and 1192 data points (607 for men, 585 for women) for the 400-m event. The standardized time for each stroke was calculated by dividing the actual time by a reference time specific to each stroke to accommodate the inherent disparities among the four strokes and the impact of the diving start in butterfly. The reference time was derived from the respective laps in single-stroke finals in the in the 2017 World Swimming Championships. A decision tree method was applied. The binary dependent variables were qualified or non-qualified in heats and semifinals, and medalists or non-medalists in finals. The independent variables were the pace in each stroke, represented by the ratio of standardized time in the specific stroke to the sum of standardized time in all four strokes. A total of 10 decision trees with the Classification and Regression Tree algorithm were established: heats, semifinals, and finals in men`s and women`s 200-m medley; and heats and finals in men`s and women`s 400-m individual medley. The decision tree models was established. The binary dependent variables were qualified or non-qualified in heats and semifinals, and winning medals in finals. The independent variables were the ratio of standardized time in each stroke to the sum of standardized time in all four strokes. The normalized importance of each stroke in each decision tree was calculated. RESULTS: In men`s and women`s 200-m and 400-m individual medley, butterfly held the highest normalized importance in winning medals in the finals. The pace in butterfly was the first node in eight of the 10 decision trees, except men`s 200-m semifinal and 400-m final, in which backstroke was the first node. The cut-off values for pace in butterfly in these eight models indicated that a pace larger than 0.236-0.245, i.e. spending relatively longer standardized time, in butterfly was associated with a higher likelihood of being qualified or winning medals in these competitions. It is noteworthy that the pace in this study is relative to each swimmer`s performance in all four strokes. CONCLUSION: Elite swimmers who spend a higher ratio of standardized time in butterfly is associated with a higher likelihood of winning medals or qualifying for the next stage in most international men`s and women`s 200-m and 400-m individual medley. Excellence in butterfly is the most crucial determinant in success in individual medley events while proficiency in at least one other stroke enhances the likelihood of winning.